Fetus in fetu: a case report (Research, Society and Development, 2022)
Fetus in fetu (FIF) is a rare benign anomalous condition, defined as the presence of a parasitic, monozygotic, and diamniotic fetus within another fetus during a pregnancy. With approximately 200 cases described in the medical literature, it is characterized by a very rare condition of great interest in the scientific community in the health area. FIF presents at different ages, being more common in childhood, more precisely in patients under 18 months of age, with few cases reported in adults. This article includes a case report of a young female patient who, at approximately 39 weeks of gestation with complications, conceived a male newborn with prenatal exams without alterations, but with physical and postnatal imaging studies compatible with fetus in fetu in Fortaleza, Ceará, Brazil. During his stay at the hospital post birth, the newborn underwent to a successful surgery to remove the fetal parts from his body. In view of what has been discussed, the importance of the topic in question can be seen, both because it is an extremely uncommon condition and because it is of great value to the scientific community in the health area.